Development of Augmented Reality Book (AR-Book) Based Science Learning Media on Human Digestive System Material to Improve Student Learning Outcomes - Dina Abdilah; Desi Wulandari (Jurnal Penelitian Pendidikan IPA, 2024)
This research was motivated by the low learning outcomes of students in science subjects of human digestive system material due to the lack of TPACK-based learning media innovations that make it easier for students to learn the material so that students feel bored with the media they have been using. The purpose of this study is to develop, test the feasibility, and test the effectiveness of Augmented Reality Book (AR-Book) media in improving learning outcomes in human digestive system material of grade V students of SDN Kalibanteng Kidul 01. This research uses the Research and Development method with the ADDIE development model. The instruments used are questionnaires and test questions. Product validity tests are carried out by material and media experts. The results of this research are: AR-Book development design as a learning medium; media notability of AR-Books by 90% media experts and 92% of materials rated "very valid"; teacher and student responses to AR-Book were "very interesting" with a percentage of teachers 92% and students 93.7%; The effectiveness of the media from the t test results showed a GIS (2-tailed) value of 0.000 < 0.05 which means there is a significant difference from the average results before treatment and after treatment and the N-Gain test which shows a value of 0.71 which means there is a significant increase in the high category. Thus, it can be concluded that the AR-Book media is very valid, very interesting, and effective for improving the learning outcomes of grade V elementary school students.